Sociological study about the effect of modernity characteristics on the ethnic identity - Khademian, Talieh (2020)
Ethnicity and nationality are types of modern social identities that have reformed after being globalized. This research tries to study the role of modernity characteristics on ethnic identity. Research data was collected using a researcher-made questionnaire, and 384 students of Islamic Azad University, Tehran North Branch were selected by non-probability random sampling in 2019. The results show the significant relationship between ethnic identity and modernity characteristics, modern lifestyle (r=-0.66), modern identity (r=-0.74), modern socialization (r=-0.40), and purposeful use of virtual social networks (r= 0.31). In other words, ethnic identities are weakened by the tendency of participants to the western beneficial and individualistic patterns and values adapted with law, avoiding and underestimating religious and traditional norms. Meanwhile, virtual social networks as a modernity tool have been an opportunity to state the ethnics political and social demands particularly frontiersmen such as Kurds and Turks. Principally, they have appeared in the form of dramatic movements and inter-ethnic tensions that following modernity elements finally reduces ethnical belongings and tendency to the global identity, and only purposeful and conscious use of virtual space can bring integrity and vitality of ethnic identity. In addition, it has unified, awakened, and sued ethnics all over the national borders because of mutual history and identity. According to the results of research, the ethnic belonging of Kurdish and Turkish students was higher than others, and these ethnicities have more complete awareness about their history, epic, land, ethnic customs, rituals, industry, style of clothing, and local cuisine. In addition, they adhered to marriage, companionship, and cooperation with their people and were proud of their native names.